2023
DOI: 10.1177/10815589231167357
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette use and prevalence of lung diseases among the U.S. population: a NHANES survey

Abstract: The primary aim of this study was to evaluate epidemiological characteristics and prevalence of lung disease among e-cigarettes users in the United States. A population-based, cross-sectional survey was performed using the National Health and Nutrition Examination Survey (NHANES) of 2015–2018. Adults using e-cigarettes (SMQ900), traditional smoking (SMQ020: > 100 cigarettes in lifetime or SMQ040: current cigarettes use), and dual smoking (e-cigarettes and traditional smoking) were identified and compared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Chronic obstructive pulmonary disease was defined as a positive response ('yes') to the question 'Ever told you had COPD?' [31]. Health-associated behaviors included alcohol intake (yes/no) and smoking.…”
Section: Covariatesmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease was defined as a positive response ('yes') to the question 'Ever told you had COPD?' [31]. Health-associated behaviors included alcohol intake (yes/no) and smoking.…”
Section: Covariatesmentioning
confidence: 99%
“…The following factors other than tobacco use affecting the occurrence of outcomes that were used in past crosssectional studies investigating the relationship of e-cigarette or HTP use to the occurrence of outcomes (COPD, 12,[16][17][18][19][20][21][22] asthma, 12,16,18,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] wheezing, 13,32,[39][40][41][42][43] breath shortness/cough/phlegm, 32,33,41,42 lung function abnormality 44 ) and cohort study 45 investigating the relationship between smoking and COPD were used as adjustment factors in this study: age, sex, BMI, resident area population size, education level, household income, whether employed or unemployed, lifestyle habits (frequency of exercise, frequency of alcohol drinking, level of stress), whether historical or concurrent diseases were present (diabetes, lipid abnormality, hypertension, stroke, allergic dermatitis/rhinitis, angina pectoris, coronary heart diseases (CHD)). Information about passive smoking was not obtained in this study, because no statistical effect from passive smoking was observed 16,39 in past cross-sectiona...…”
Section: Confounding Factorsmentioning
confidence: 99%